The forgotten : a Peter Decker/Rina Lazarus novel - Kellerman, Faye. (New York Morrow, 2001)
Having submitted for counseling a troubled wealthy teen who desecrated a synagogue, Rina Lazarus discovers there is more to the case when the boy and his therapists are murdered.
"A Peter Decker/Rina Lazarus novel" --cover
Keywords: Decker, Peter (Fictitious character) -- Fiction; Lazarus, Rina (Fictitious character) -- Fiction; Mystery fiction